2008
DOI: 10.1097/brs.0b013e31816f69b3
|View full text |Cite
|
Sign up to set email alerts
|

Fusion Rates After Thoracoscopic Release and Bone Graft Substitutes in Idiopathic Scoliosis

Abstract: Demineralized bone matrix (Grafton DBM Flex) seem to be an effective bone graft substitute in thoracoscopic surgery for idiopathic scoliosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Price et al retrospectively analyzed the efficacy of DBM in combination with bone marrow for a posterior spinal fusion in 77 scoliosis cases, and found that the fusion rates were comparable to those of iliac bone autograft combined with DBM composites [47]. Weinzapfl et al [48] compared the use of allograft to DBM as a bone graft substitute in patients undergoing video assisted anterior thoracoscopic release and fusion for adolescent idiopathic scoliosis. At more than 1-year follow-up, fusion was observed on lateral radiographs in 82 % of the disc spaces in the allograft group and in 92 % in the DBM group, although this difference was not significant.…”
Section: Demineralized Bone Matrixmentioning
confidence: 99%
“…Price et al retrospectively analyzed the efficacy of DBM in combination with bone marrow for a posterior spinal fusion in 77 scoliosis cases, and found that the fusion rates were comparable to those of iliac bone autograft combined with DBM composites [47]. Weinzapfl et al [48] compared the use of allograft to DBM as a bone graft substitute in patients undergoing video assisted anterior thoracoscopic release and fusion for adolescent idiopathic scoliosis. At more than 1-year follow-up, fusion was observed on lateral radiographs in 82 % of the disc spaces in the allograft group and in 92 % in the DBM group, although this difference was not significant.…”
Section: Demineralized Bone Matrixmentioning
confidence: 99%
“…Four DBM products have been used in spinal surgery: Accell Connexus (Citagenix, Laval, Canada); Allomatrix; Grafton DBM; and Osteofil (Medtronic, Minneapolis, Minnesota). These DBM products were used as bone graft extenders in most studies; only in two studies 45 , 46 was Grafton DBM used as a bone graft substitute.…”
Section: Resultsmentioning
confidence: 99%
“…Grafton DBM was the only product also used for thoracic fusions. In a retrospective cohort, Weinzapfel et al 46 used Grafton DBM in patients who underwent anterior thoracic discectomies and compared their results with using morsellised cancellous allografts. On the final radiographs, 82% of the allograft group and 92% of the Grafton DBM group were rated as fused.…”
Section: Resultsmentioning
confidence: 99%
“…The greatest number of references were related to its usage in spinal fusion for deformity. 21,44,[53][54][55] Hedequist recently reported that freeze-dried allograft was equivalent to autograft for treatment of congenital scoliosis, an important finding as autograft for most of these children is not adequate. 56 There are also favorable report of its usage for treatment of benign and malignant bone tumors, 53,57 for foot osteotomies, 58,59 and iliac osteotomies.…”
Section: Pediatric Orthopaedic Applicationsmentioning
confidence: 99%